Is there a difference in clinicopathological outcomes of renal tumor between young and old patients? A multicenter matched-pair analysis. (2nd September 2016) - Kim, Jeong Ho; Park, Yong Hyun; Kim, Yong June; Kang, Seok Ho; Byun, Seok Soo; Hong, Sung-Hoo
Abstract: Objective: The aim of this study was to investigate the influence of age at diagnosis on tumor characteristics and cancer-specific survival (CSS) in renal cell carcinoma (RCC). Materials and methods: Data of patients who underwent radical or partial nephrectomy for renal tumor between 2003 and 2011 at multiple institutions were collected. Patients were divided into two groups according to age at diagnosis: 20–39 years and 40–79 years. To adjust for potential baseline confounders, propensity score matching was performed. Results: All included data showed that young RCC patients presented with renal tumors that had a more favorable histological subtype, were localized, smaller in size, and had a lower Fuhrman nuclear grade. The 5 year CSS rates were 95.5% and 90.5% in the young and old patient groups, respectively (log rank p  = 0.019). After matching on the propensity score, the two groups with RCC had 302 patients each. Because the groups were matched on covariates, there were no significant differences in the pathological proportion, tumor size, Fuhrman nuclear grade and clinical T stage. The 5 year CSS rates were 95.5% and 94.7% in the young and old patient groups, respectively (log rank p  = 0.184). Conclusion: After adjusting for potential biases, there was no significant difference in prognosis between young and old patients with RCC.